Development of low-carbon technologies in China's integrated hydrogen supply and power system - Dai-Wei Li; Jun-Ling Huang; Dan Yu; Da Zhang; Xi-Liang Zhang (Advances in Climate Change Research)
Hydrogen and electricity are crucial and interdependent energy carriers in China's pursuit of carbon neutrality, suggesting the necessity of utilizing cost-effective low-carbon technologies that facilitate their integrated development. The cost-optimal, provincial level, deployment of low-carbon technologies under this long-term goal remains to be determined. This study employs the REPO model to identify the cost-optimal, low-carbon hydrogen production mixes and the evolution of the integrated power system of China from 2020 to 2050. The integrated planning and operation of hydrogen supply and power systems are explored at the provincial level. The role of high-temperature gas-cooled reactors in this integrated energy system is also analyzed. The results reveal that electrolytic hydrogen would dominate China's hydrogen supply after 2040, with alkaline, proton exchange membrane, and solid oxide electrolyzers produce over 1 Mt of hydrogen in the short term, by 2035, and in 2050. Leveraging the low-carbon heat production of high-temperature gas-cooled reactors in addition to its electricity generation to meet the thermal requirements of solid oxide electrolyzers could boost the output to 4.2 Mt in 2050 and reducing the total system CO2 emissions and costs by 2.28% and 0.05%, respectively. By 2050, the integration of hydrogen supply and power systems also generates up to 2194 TW h of flexible electricity demand by electrolyzers, which raised the renewable energy penetration by 4 percentage points while decreasing the need of flexible natural gas power generations and energy storages. This study is valuable for proposing the analytical framework and performing the provincial-level study of decarbonization of China's integrated hydrogen supply and power system.